Global Warming Amplifies Outdoor Extreme Moist Heat During the Indian Summer Monsoon - Anukesh Krishnankutty Ambika; Akshay Rajeev; Matthew Huber (Earth's Future)
Abstract Because of the climatological prevalence of hot, humid conditions, moist heat extremes are a significant challenge to the health and wellbeing of the people in India. While research has demonstrated the importance of summer monsoon to moist heat in India, impact of monsoon‐break and warm spells in modulating extreme moist heat regionally has not been fully investigated. Here we investigate moist heat extremes, as measured by the Wet‐Bulb Globe Temperature (WBGT) metric, specifically during monsoon and monsoon‐break periods and find that they pose a major threat to physical labor and health relative to other seasons. During the 1951–2020 break period, an increase in area exposed (∼42.76 million km2), representing at least 670 million people, to extreme and detrimental WBGT values >31°C occur. Our results imply that future studies on extreme moist heat must pay close attention to the variation of weather systems on synoptic to subseasonal time scales that are superimposed on the seasonal monsoon migration.